Study of analgesic and myotropic spasmolytic activity of alkylcarb - Naboka, Olga; Kotvitska, Alla; Volkova, Alina; Tkachenko, Oksana; Voronina-Tuzovskykh , Yuliya; Filiptsova, Olga; Pasynchuk, Inna (ScienceRise: Biological Science, 2023)
The work is devoted to the search for new biologically active substances in a series of alkylamides of dihydroquinoline-3-carboxylic acid. Analgesic properties of 30 newly synthesized substances were studied, which made it possible to identify the leader compound (provisional name alkylcarb) and recommend its effectiveness for further research as an antispasmodic agent for pain relief. It has been established experimentally, that the substance alkylcarb exhibits concentration-dependent vasodilatory properties in vitro on segments of the thoracic aorta of rats. The data, obtained in the work, justify the prospect of using the leader substance as a new analgesic and antispasmodic drug. The research expands and deepens knowledge about the pharmacological properties of alkylamide derivatives of dihydroquinoline-3-carboxylic acid. The aim of the work was to conduct screening studies to establish the analgesic activity of a newly synthesized series of chemical compounds among alkylamides of dihydroquinoline-3-carboxylic acid and to study the myotropic spasmolytic activity of the leader substance. Materials and methods. Analgesic properties of alkylamides of dihydroquinoline-3-carboxylic acid were studied on outbred white mice in the "acetic acid convulsions" test. During the experiment, the animals were treated in accordance with the International Principles of the European Convention for the Protection of Vertebrate Animals Used for Experiments and Other Scientific Purposes (Strasbourg, March 18, 1986). The studied substances were administered intragastrically to experimental animals at a dose of 10 mg/kg in the form of a finely dispersed aqueous suspension, stabilized with Tween-80. Voltaren at a dose of 8 mg/kg, recommended for preclinical studies, and analgin at a dose of 50 mg/kg were chosen as reference drugs. The studies of the contractile activity of smooth muscle vessels were carried out on segments of the thoracic aorta of rats of both sexes weighing 180-200 g. The studies of dilator reactions were carried out against the background of preliminary contraction with phenylephrine at a concentration of 10-6 mol/l. The antispasmodic efficiency of the new compound was determined in comparison with the classic antispasmodic drotaverine. The statistical processing of the results was carried out using the package of statistical analysis of electronic spreadsheets Exel, with the help of the program "Statgraphics Plus v. 3.0.” and the standard package of statistical programs "Statistica, V. 6.0". We used the Student’s test, a non-parametric analog of univariate variance analysis - the Kruskal-Wallis test, and the Mann-Whitney test. Differences were considered statistically significant at p<0.05. Results. The study of the analgesic activity of substances АO1-АO30 in the "acetic acid convulsion" test in mice showed that a compound АO26 (provisional name alkylcarb) has the most pronounced analgesic activity when administered intragastrically. In the "acetic acid convulsion" test, alkylcarb (10 mg/kg, per os) probably reduces the number of convulsions, caused by acetic acid. The level of activity of this compound is comparable to the activity of diclofenac (8 mg/kg, per os) and exceeds analgin (50 mg/kg, per os). The substance alkylcarb relieved vasospasm at the level of the comparison drug drotaverine in in vitro experiments on a model of an isolated fragment of the thoracic aorta of rats against the background of previous constriction with phenylephrine. Conclusion. Today, the search for new highly effective non-opioid analgesics is an urgent problem of modern pharmacology, since painkillers used in clinical practice do not meet the requirements of efficiency and safety. In this regard, in recent years, scientists of the National Pharmaceutical University have been intensively searching for new, highly effective substances with antinociceptive, anti-inflammatory and antipyretic effects among alkylamides of dihydroquinoline-3-carboxylic acid.